POTENSI DAYA TARIK WISATA NAGARI TUO PARIANGAN SEBAGAI KAWASAN DESA WISATA PARIANGAN KABUPATEN TANAH DATAR SUMATERA BARAT - Dini Masly; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine: (1) The potential of Tourist attractions Nagari Tuo Pariangan; (2) The government's efforts to develop tourist attractions.This study used a qualitative method with descriptive approach, this subjects of this study werw taken from including, local community and village heads of Nagari Tuo Pariangan. The data collection is made by a study of documents, observation, interview, documentation.The results showed that Pariangan village has tourism potential, nature tourism attractions, cultural tourism attractions and specialist attractions , the potential of natural attractions, consist hot springs, Najun waterfall, forest and flora, the potential culture attraction and surrounding a tourist area of traditional and unique village including, aqikah, circumcision apostles / circumcisions, batagak penghulu tradition, marriage tradition and way of life, this village has a high social life marked by frequent public conduct mutual cooperation. In conclusing Pariangan village was potentially to be developed as a tourist village, supported by the efforts to develop infrastructure improvements as well as promotion.Keywords : Tourist area, attraction, Nagari Tuo Pariangan